Esophageal oxyhemoglobin saturation as a resuscitative metric in hemorrhagic shock - Julia Garcia Mancebo; Kristen Sack; Padraic Romfh; Yifeng Peng; John Kheir (Trauma Surgery & Acute Care Open)
Background Mixed venous saturation (SvO2) is considered the gold standard to assess the adequacy of tissue oxygen delivery (DO2) in shock states. However, SvO2 monitoring is challenging as it requires an invasive catheter and frequent blood sampling. Non-invasive methods, including near-infrared spectroscopy, have demonstrated low sensitivity to tissue dysoxia.Methods We fabricated a new device that uses resonance Raman spectroscopy (RRS) to quantify oxyhemoglobin saturation (ShbO2) in the esophagus (eShbO2), tongue (tShbO2), and liver (hShbO2). In two rat models of hemorrhagic shock, we quantified (1) The correlation of RRS-measured ShbO2 to SvO2 during progressive hemorrhage (n=20) and (2) The value of these metrics to predict near-term mortality in fixed, severe hemorrhage (mean blood pressure =25 mm Hg; n=18).Results In model 1, eShbO2 (r=0.705, p<0.0001) and tShbO2 (r=0.724, p<0.0001) correlated well with SvO2 and with serum lactic acid (eShbO2-lactate r=0.708, p<0.0001; tShbO2-lactate r=0.830, p<0.0001). hShbO2 correlated poorly with both SvO2 and lactic acid. Using time-matched ShbO2-SvO2 pairs, the performance of ShbO2 to detect severe tissue hypoxia (SvO2<20%) was excellent (AUC 0.843 for eShbO2, 0.879 for tShbO2). In model 2, eShbO2 showed a maximized threshold of 40% with 83% of animals dying within 45 minutes of this cut-off, demonstrating accuracy as a monitoring device. This was similar for tShbO2, with a threshold of 50%, predicting death within 45 minutes in 76% of animals. ShbO2 showed superior sensitivity to invasive monitoring parameters, including MABP<30 mm Hg (sensitivity 59%), pulse pressure<15 mm Hg (sensitivity 50%), and heart rate>220 bpm (sensitivity 39%, p=0.004).Conclusions eShbO2 represents a new paradigm to assess the adequacy of DO2 to a tissue. It constitutes a promising monitoring method to evaluate tissue oxygen saturation in real time and non-invasively, correlating with SvO2 and time to death.Level of evidence Level III, therapeutic/care management.